PENGARUH DIMENSI KETERIKATAN KARYAWAN TERHADAP KINERJA KARYAWAN PADA KANTOR DIREKSI PT PERKEBUNAN NUSANTARA VII - Saputra, Renja Wahyu; Jimad , Habibullah; Karim, Mirwan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The aim of the research is to ascertain how the employee engagement dimensions affect the directors of PT Perkebunan Nusantara VII's employees' performance. The information gathered from 136 respondents in the sample was obtained using a Likert scale questionnaire. The data research is analyzed using the t-test and multiple linear regression. The findings indicate that employee performance is positively and significantly impacted by the vigor, devotion, and absorption dimensions.